Analysis Optical Properties of Carbon Dots from Paper Flowers (Bougainvillea spectabilis) - Ramlan, Nurul Mutmainnah; A'yun, Arini Qurrata; Putri, Radha Hartina; Fatimah, Siti; Isnaeni, .; Tahir, Dahlang (Omega: Jurnal Fisika dan Pendidikan Fisika, 2018)
Synthesized carbon dots (CDs) from paper flowers (Bougainvillea spectabilis) was performed by microwave assisted. CDs were characterized by ultraviolet visible light (UV-Vis), photoluminescence (PL) and time resolved luminescence (TRPL). PL data shows wavelength intensity of CDs paper flowers at 493 nm for 3.9 ns and 512 nm for 4.2 ns respectively for purple and white paper flowers that excited at 420 nm. The absorbance for CDs white paper flower at 262 nm and 350 nm, while CDs purple flower paper at 260 nm, 324 nm, and 530 nm. CDs from paper flower shows excellent optical properties. So, it is mean that method applied to this experiment effectively, cheap and eco-friendly for synthesis CDs from paper flower.